Medieval Communities and the Mad : Narratives of Crime and Mental Illness in Late Medieval France - Pfau, Aleksandra (Book collections on Project MUSE., 2021)
In medieval France, the collaboration between local communities and greater authorities grants us unusual insight into the period's concept of madness. The mentally ill posed a unique challenge to the law, and, by examining how subjects and officials worked together to define and contain mad individuals, this book analyses the development of that law and the interaction between local and regional communities. The author argues that this struggle often strengthened communities and proto-national identities.